Humanized Artificial Body in the 20th Century Italian Literature - Elena Yu. Saprykina (Studia Litterarum)
In various epochs, science fiction writers shared an interest in problems related to the humanization of an artificial body and the process of human interaction with a man’s own creation. In the 20th century Italian literature, in particular, this theme emerged already at the dawn of the century (e.g. а futuristic novel by F.T. Marinetti) and was present up until the beginning of the current “age of artificial intelligence.” Fantastic plots of several short stories and novellas by D. Buzzati and T. Landolfi, written in the 1950s and 60s, depicted ambivalent perception of the technogenic civilization and its novelties by the modern cultural consciousness. On the one hand, these works reflected the turning of the machine into an indispensable attribute of the social status of the modern human, the guarant of her private life success and mental health. On the other hand, in science fiction, there is a clear tendency to dramatize the problems and difficulties that the technological age set for a human — in particular, the problem of preserving the privilege of the human consciousness over the increasingly sophisticated artificial intelligence of the machine.